Integrin-specific signaling pathways controlling focal adhesion formation and cell migration - Mostafavi-Pour, Zohreh (The Rockefeller University Press, 2003)
The fibronectin (FN)-binding integrins α4β1 and α5β1 confer different cell adhesive properties, particularly with respect to focal adhesion formation and migration. After analyses of α4(+)/α5(+) A375-SM melanoma cell adhesion to fragments of FN that interact selectively with α4β1 and α5β1, we now report two differences in the signals transduced by each receptor that underpin their specific adhesive properties. First, α5β1 and α4β1 have a differential requirement for cell surface proteoglycan engagement for focal adhesion formation and migration; α5β1 requires a proteoglycan coreceptor (syndecan-4), and α4β1 does not. Second, adhesion via α5β1 caused an eightfold increase in protein kinase Cα (PKCα) activation, but only basal PKCα activity was observed after adhesion via α4β1. Pharmacological inhibition of PKCα and transient expression of dominant-negative PKCα, but not dominant-negative PKCδ or PKCζ constructs, suppressed focal adhesion formation and cell migration mediated by α5β1, but had no effect on α4β1. These findings demonstrate that different integrins can signal to induce focal adhesion formation and migration by different mechanisms, and they identify PKCα signaling as central to the functional differences between α4β1 and α5β1.